(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
The study aims to analyze thermal oxidative stability of repeatedly heated corn oil with particular reference to α-tocopherol and β-carotene. Current study evaluated stability of phytosterol, phenols, α-tocopherol, and β-carotene in corn oil submitted to thermal degradation following repeated heating at 100°C and 180°C. The oxygenated samples were repeatedly collected following 5 hours of heat exposure three times a day for three days and stored in amber-colored bottles. Oil samples were subjected to physicochemical parameters along with a quantitative estimation of total phytosterol, total phenols, α-tocopherol, and β-carotene. Thermal degradation at 180°C had elevated density, viscosity, acid value, and peroxide value significantly (P<0.05-0.001), whereas it reduced iodine value and specific gravity. Oxidation of corn oil at 180°C showed 79.18% and 43.75% loss of α-tocopherol and β-carotene content. Heating corn oil three times a day for five hours over three days results in considerable degradation and darkening of color with a subtle increase in opacity, increased viscosity, density, peroxide value, and acid value, alongside a notable decline in α-tocopherol and β-carotene content. Thermal oxidation led to formation of oxidized products, resulting in notable alterations in corn oil's physicochemical and phytochemical characteristics, compromising its health benefits.